Advancements in the Study of Biologic Agents in Comorbidities of Psoriasis: A Literature Review - Wang Y; Zhang P; Lv Y; Deng Y; Yao M; Wang L; Pan G (Dove Medical Press, 2023)
Yuhan Wang,1,* Ping Zhang,1,* Yu Lv,1 Yu Deng,2 Ming Yao,3 Lin Wang,1 Guangtao Pan3 1College of Traditional Chinese Medicine, Hubei University of Chinese Medicine, Wuhan, Hubei Province, People's Republic of China; 2Department of Encephalopathy, Guangzhou Hospital of Integrated Traditional and West Medicine Affiliated to Guangzhou University of Chinese Medicine, Guangzhou, People's Republic of China; 3Department of Dermatology, Yancheng Hospital of Traditional Chinese Medicine Affiliated to Nanjing University of Chinese Medicine, Yancheng, Jiangsu Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Guangtao Pan, Department of Dermatology, Yancheng Hospital of Traditional Chinese Medicine Affiliated to Nanjing University of Chinese Medicine, No. 53, Renmin North Road, Tinghu District, Yancheng, Jiangsu Province, People's Republic of China, Tel +86-17612738767, Email panguangtaowuhan@foxmail.comAbstract: This literature review systematically searched relevant literature from the past 10 years using various medical databases, including PubMed, Medline, Cochrane, China National Knowledge Infrastructure (CNKI), Wanfang, and Weipu. As a chronic inflammatory disease, psoriasis is associated with various cells and cytokines of the body's immune system, making them more susceptible to various systemic comorbidities than the general population. At a time when conventional regimens are ineffective and there is a lack of personalized treatment options for such comorbidities, the development of biologics has revolutionized the treatment of psoriasis comorbidities, and a number of biologic combination therapies have been incorporated into first-line treatments in many countries. The focus of this review was to investigate the relationship between psoriasis and comorbidities, such as metabolic syndrome, psoriatic arthritis, cardiovascular diseases, mental disorders, infectious diseases, digestive system diseases, and renal diseases. Furthermore, the study explored the significance of biologic therapies in the management of these comorbidities. Also this paper suggests current conditions and precautions for the use of biologic therapies to minimize the occurrence of adverse effects. This review was performed to provide guidance for clinical drug selection in patients with psoriasis and comorbidities, as well as serve as a reference for the development and application of biologic therapies.Keywords: psoriasis, biologics, comorbidity, research advancements